2005
DOI: 10.1002/macp.200400309
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Behavior of TiO2 Nanoparticles in LLDPE/LDPE/TiO2 Nanocomposites

Abstract: Summary: TiO2 nanoparticles were introduced into linear low‐density polyethylene (LLDPE)/low‐density polyethylene (LDPE) composite films in the form of master batch where TiO2 was pre‐dispersed in LDPE by melt compounding. The dispersion behavior of TiO2 nanoparticles was investigated by field‐emission scanning electron microscopy (FE‐SEM). The rheology results show that the viscosity of LDPE/TiO2 master batch is lower than that of LLDPE/LDPE composites. Energy dispersive X‐ray spectrometer (EDS) composition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The attachment of Ag + from the TiO 2 NPs may bestow antimicrobial properties. [5,8] Gupta et al [26] reported that Ag-TiO 2 nanocomposites having Figure 11. (a and b) LDPE produced using 0.5% Ag and 2.5% TiO 2 as well as 1% of silver, which were produced by the sol-gel method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The attachment of Ag + from the TiO 2 NPs may bestow antimicrobial properties. [5,8] Gupta et al [26] reported that Ag-TiO 2 nanocomposites having Figure 11. (a and b) LDPE produced using 0.5% Ag and 2.5% TiO 2 as well as 1% of silver, which were produced by the sol-gel method.…”
Section: Discussionmentioning
confidence: 99%
“…According to the method of Wang and colleagues, [5] the samples were completely cleaned and dried to obtain a high energy electron beam for imaging and chemical analysis. The samples were placed on stubs, and electrical contact between the stubs and samples was generated.…”
Section: Survey Of Features Of the Produced Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Chaichana et al [16] developed a novel route to synthesize linear low density polyethylene (LLDPE)/nanosilica systems via in situ polymerization with a zirconocene/methyl alumoxane (MAO) catalyst, in order to study the effect of particle size on the catalytic properties of the resulting materials. The effect of silica and zirconia nanoparticles on the microstructure of LLDPE nanocomposites synthesized via in situ polymerization with zirconocene was investigated by Jongsomjit et al [17], while Wang et al [18] analyzed the dispersion behaviour of titania (TiO 2 ) nanoparticles in polyolefin nanocomposites. In recent years an extended investigation was carried out by this research group on the viscoelastic and the fracture behavior of polyolefin based nanocomposites [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%